Pengaruh Good Corporate Governance pada Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi - Dika Putra, Gede Marco Pradana; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2020)
A firm not only aims to get profits but also maximize its value  which can be reflected in stock price. Research aims to examine the effect of good corporate governance on firm value with financial performance as a mediating variable. The study conducted on LQ45 companies listed on Indonesia Stock Exchange in 2017-2018. Sample determined by purposive sampling with 32 samples. Path analysis was used. analysis showed managerial ownership and institutional ownership had no effect on financial performance, managerial ownership and institutional ownership had no effect on firm value, financial performance had a positive effect on firm value, and financial performance was unable to mediate the relationship between GCG and firm value. Keywords: Good Corporate Governance; Firm Value.